Students Cognitive Development in Basic Level Schools in Nepal: Provisions and Practices - Paudel, Mohan; Acharya, Kamal Prasad; Acharya, Milan (Journal of Advanced College of Engineering and Management, 2023)
This study explores the current status of basic-level students’ cognitive learning and examines how school education provisions are functioning to facilitate perceptive education. The study was conducted by adopting a mixed-method research design, including a quantitative survey and a qualitative case study for data generation from six schools in four districts across the country. With a small research grant support from UNESCO Nepal, this research was conducted under the Centre for Educational Research, Innovation and Development (CERID) to provide a new and innovative concept to learning from different aspects ranging from knowing to creating. Students’ achievement at six levels of cognitive development was evaluated based on a questionnaire containing items from the revised Bloom's taxonomy of educational objectives. Classroom practices were systematically observed, and the main events and activities were recorded. The study revealed that the students performed better in remembering and showed lower performance at creating level. Classroom pedagogies were found dominantly lecture-based and concentrated around the acquisition of knowledge from the textbook. Besides, teachers were found not preparing the lesson plan, nor were they taking classes in a planned way. There was no plan, program, or practice regarding cognitive teaching-learning for addressing the specific potentials, weaknesses, and aptitudes of students at the basic level of education in Nepal.